Spatial Income and Purchasing Power Disparities in the Context of the Policy Goal of Equivalent Living Conditions in Bavaria - Swiaczny, Frank; Sulak, Harun; Klüsener, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
The spatial differences in income in Bavaria were examined in the context of the goal of equivalent living and working conditions anchored in the Bavarian constitution and state planning. Disparities in income distribution, taking into account spatial differences in purchasing power, are of central importance as a measure of equal living conditions. The presented analysis of spatial income disparities uses consistent time series data for the Bavarian counties in the period 1991 to 2018, which were determined as part of the national accounts. Using the Theil index, it can be shown for Bavaria that spatial disparities in the primary income of counties are significantly reduced by taxes and social benefits, and have generally decreased in recent decades. This applies both to differences between and within administrative districts, as well as to differences between and within types of counties which reflect the degree of urbanisation. An adjustment for regional housing costs further reduces spatial disparities in material living standards, whereby large-scale interregional differences become less significant.
Keywords: Spatial planning; Equivalent living conditions; Spatial income disparities; Bavaria